Morphological Errors In The Ten Wazan For The Writing Skill Of Non-Native Arabic Language Learners/ الأخطاء الصرفية في الأوزان العشرة بمهارة الكتابة لدى متعلمي اللغة العربية الناطقين بغيرها - Khamaiseh, Mohammad Ahmad; Osman, Norasyikin; Elawadi, Elsayed Mohamed Salem (Ijaz Arabi Journal of Arabic Learning, 2024)
This study aimed to identify the morphological errors made by Arabic language learners who are native speakers of other languages while learning the ten Arabic verb forms (weights). The study employed a quantitative approach to achieve its objectives. The study sample was conveniently selected and consisted of 123 third and fourth-year students majoring in Arabic language studies at the College of Languages and Communication at Sultan Zain Al-Abidin University. A questionnaire was prepared to achieve the study's objectives, and a test was conducted to measure the student's ability to recognize and extract the ten verb forms from texts and differentiate between them. The results showed that the most common errors made by Arabic language learners about the ten verb forms were in their writing skills and were of a high degree. The results also revealed differences among the study community members in recognizing the ten morphological forms attributed to academic level, with these differences favoring the fourth year. The study results indicated no statistically significant differences in identifying the ten morphological forms attributed to gender.